Analisis Faktor – Faktor yang Mempengaruhi Perbedaan Inflasi Aktual dan Inflasi Target - Ruth Kartika Mardiana (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This research investigates the factors that influence differences of inflation actual and inflation targets. Variables is used in this research are money supply, BI Rate as monetary sectors and oil price international, gold price as nonmonetary sectors. The research use logit model analysis and correlation analysis. The result showed that the variable money suuply, BI Rate, Oil price international, Gold Price doesn’t have significant effect on the difference of inflation actual and inflation targets. Because doesn’t significant, but added correlation analysis with nonmonetary sector were inflations was seen from seven groups of goods and inflation by types. The result showed that from seven groups of good there four groups was correlate.And from inflation by types there all types was correlate. But, the most correlate was nonmonetary to differences of inflation.Keywords: inflation Actual, inflation targets, monetary sector, non monetary sector, logit model, correlation